Differential proteomic responses of selectively bred and wild-type Sydney rock oyster populations exposed to elevated CO2 - Thompson, E L; O'Connor, W A; Parker, L; Ross, P; Raftos, D A (Molecular Ecology, 2015)
Previous work suggests that larvae from Sydney rock oysters that have been selectively bred for fast growth and disease resistance are more resilient to the impacts of ocean acidification than nonselected, wild-type oysters. In this study, we used proteomics to investigate the molecular differences between oyster populations in adult Sydney rock oysters and to identify whether these form the basis for observations seen in larvae. Adult oysters from a selective breeding line (B2) and nonselected wild types (WT) were exposed for 4 weeks to elevated pCO2 (856 μatm) before their proteomes were compared to those of oysters held under ambient conditions (375 μatm pCO2). Exposure to elevated pCO2 resulted in substantial changes in the proteomes of oysters from both the selectively bred and wild-type populations. When biological functions were assigned, these differential proteins fell into five broad, potentially interrelated categories of subcellular functions, in both oyster populations. These functional categories were energy production, cellular stress responses, the cytoskeleton, protein synthesis and cell signalling. In the wild-type population, proteins were predominantly upregulated. However, unexpectedly, these cellular systems were downregulated in the selectively bred oyster population, indicating cellular dysfunction. We argue that this reflects a trade-off, whereby an adaptive capacity for enhanced mitochondrial energy production in the selectively bred population may help to protect larvae from the effects of elevated CO2, whilst being deleterious to adult oysters. © 2015 John Wiley & Sons Ltd.